2018
DOI: 10.3390/su10103726
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Governance of Energy-Neutral Housing: Toward a Framework for Analysis

Abstract: Regions are expected to play a key role in realizing international, European, and national climate and energy goals. Also regions in the Netherlands are working toward these goals, taking initiatives toward an energy-neutral built environment by 2050. However, it remains unclear how such efforts and other socially innovative activities can best be described and how variation between them in terms of governance can be explained. In this article, we develop a framework for analyzing the governance of regional en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In line with De Leeuw and Groenleer [15] the WB case showed that regional governance processes take place in the shadow of policy developments at the national level, and even to the extent that ongoing negotiations in policy making at the national level create a high degree of uncertainty. This leads to inaction at the regional level with stakeholders refraining from action because they perceive high uncertainty with regard to the key future policy instruments that will eventually be introduced, and the consequences this will likely have on the level playing.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…In line with De Leeuw and Groenleer [15] the WB case showed that regional governance processes take place in the shadow of policy developments at the national level, and even to the extent that ongoing negotiations in policy making at the national level create a high degree of uncertainty. This leads to inaction at the regional level with stakeholders refraining from action because they perceive high uncertainty with regard to the key future policy instruments that will eventually be introduced, and the consequences this will likely have on the level playing.…”
Section: Discussionmentioning
confidence: 64%
“…'Policy mixes' retrieved in the cases revealed a comprehensive picture, but also showed the need for particular instruments like Green Deals and covenants to deal with the innovative and comprehensive nature of regional energy project covering cross-jurisdictional boundaries in complex multi-actor settings (e.g., in the A16 and Amernet cases). Perhaps, it is fair to state that comprehensive 'policy mixes' were required to deal with the lack of systemic innovation structures regarding energy transition in the WB region, arguably as new governance arrangements, social innovations [15,80], or even 'proto-innovation systems' [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations